2020
DOI: 10.1080/20430795.2020.1749819
|View full text |Cite
|
Sign up to set email alerts
|

Does sharia governance influence corporate social responsibility disclosure in Indonesia Islamic banks?

Abstract: Purpose: This study aims to investigate the effect of sharia governance to corporate social responsibility disclosure in Indonesia Islamic banks. Design/methodology/approach: The data in this study are taken from the annual reports of ten Islamic banks in Indonesia in the period 2011-2018. The data analysis method used in this study is multiple linear regression analysis. Findings: This study finds that the effectiveness of the board of directors plays a vital role in enforcing corporate social responsibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 81 publications
(86 reference statements)
2
27
1
1
Order By: Relevance
“…The ethical responsibility of SOEs/ROEs is to give the best service to the consumer, allowing the consumer to complain, give fair compensation, and always follow the regulation. The findings of this study are in line with the opinion of Vergalli & Poddi (2009), which stated that companies performing social responsibility would have long-term performance (De Giovanni, 2012;Iqbal & Parwati, 2013;Margolis & Walsh, 2003;Muliati, 2014;Ridwan & Mayapada, 2020;Stefan & Paul, 2008;Valmohammadi, 2014).…”
Section: The Effect Of Social Responsibility On Firm Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…The ethical responsibility of SOEs/ROEs is to give the best service to the consumer, allowing the consumer to complain, give fair compensation, and always follow the regulation. The findings of this study are in line with the opinion of Vergalli & Poddi (2009), which stated that companies performing social responsibility would have long-term performance (De Giovanni, 2012;Iqbal & Parwati, 2013;Margolis & Walsh, 2003;Muliati, 2014;Ridwan & Mayapada, 2020;Stefan & Paul, 2008;Valmohammadi, 2014).…”
Section: The Effect Of Social Responsibility On Firm Performancesupporting
confidence: 90%
“…Similarly, Muliati (2014) found that the disclosure of social responsibility that reflects the corporate social responsibility activities that have been done affects the company's environmental performance. Thus, organizations that implement CSR practices also report better organizational performance (Ridwan & Mayapada, 2020). Based on the above description, the hypothesis is proposed as follows:…”
Section: The Effect Of Social Responsibility On Firm Performancementioning
confidence: 99%
“…Stakeholders include employees, creditors, suppliers, customers, and local communities (Mallin et al, 2014). All stakeholders contribute to an enterprise so the enterprise should pay attention to the related interests (Ridwan & Mayapada, 2020…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, some variables have the opposite influence with CSRD including accounting experts on the board, politicians on the board and audit committee size. Ridwan and Mayapada (2020) studied Islamic banks in Indonesia in the period 2011-2018. The article uses OLS to examine.…”
Section: Literature Reviewmentioning
confidence: 99%